An Evaluation on Carbon Footprint Indicators in Turkey Located Banks and Worldwide Banks - (:unkn) unknown (IGI GLOBAL, 2019)
Global warming has become one of the most critical issues in the recent years. There is a great debate, centered on greenhouse gas emissions of countries, companies, and institutions. Not only the manufacturing sector but also service sector has begun to be questioned in terms of the need for controlling greenhouse gases. Thus, banks deserve an attention on the basis of sustainability and environmental impact. Besides the operational activities of this enormous sector, its investing and lending choices have considerable influence on sustainability. The carbon footprint measurement indicators have to be standardized in order to estimate the contributions of the banks in the global climate change precisely. In this study, carbon footprint measurement indicators, extracted from the sustainability reports and/or websites of the banks in Turkey are examined The findings have been comparatively discussed with the measurements used by the international banks and addressed in the literature.
Keywords: Banking Sector; Carbon Emissions; Carbon Footprint; Carbon Footprint Indicators; Service Sector